Pengaruh Suplementasi Zinc terhadap Waktu Penyembuhan Luka Perineum pada Ibu Nifas - Jamhariyah Jamhariyah (Politeknik Negeri Jember, 2017)
Zinc is a major mineral that the body needs during wound healing. Zinc supplementationhas been widely used as a major component for burns, diaperash due to lessions and other conditions. Perineal wound healing period in the normal puerperal women are 6-7 days. The purpose of this study was to determine the effect of Zinc supplementation on wound healing time of the perineum in the region Arjasa Public Health Center in 2015. The research method uses quasie experimental design with the design of the control group post test only. Its population is experiencing post partum mothers spontaneous rupture in the work area as much as 28 post partum mothers in Arjasa Public Health Center. Sampling was done by accidental sampling technique. The sample consisted of 26 post partum women who experienced spontaneous rupture. Of this sample there are 23 postpartum women were given supplements of Zinc and 23 postpartum women were not given zinc supplements. Results of data analysis using independent test two sample t-test obtained uncorrelated t count is greater thant t table (5.377>2.063), meaning that Ho is rejected. This shows there are influence of Zinc supplementation on perineal wound healing time in postpartum mother. Based on the results of this study, Zinc was instrumental in the proliferatife phase constriction of blood vessels and accelerate the formation of new networks of fibrin fibers that time faster wound healing. Keywords : Zinc supplementation, perineal wound healing time